SuperSour: A New Strategy for Breeding Superior Citrus Rootstocks - Bowman, Kim D.; McCollum, Greg; Albrecht, Ute (Frontiers in Plant Science, 2021)
Citrus crops have a long history of cultivation as grafted trees on selected rootstock cultivars, but all current rootstocks have significant limitations and traditional methods of rootstock breeding take at least 2-3 decades to develop and field test new rootstocks. Citrus production in the US, and other parts of the world, is impaired by a wide range of biotic and abiotic problems, with especially severe damage caused by the disease huanglongbing (HLB) associated with Candidatus Liberibacter asiaticus. All major commercial citrus scion cultivars are damaged by HLB, but tree tolerance is significantly improved by some rootstocks. To overcome these challenges, the USDA citrus breeding program has implemented a multi-pronged strategy for rootstock breeding that expands the diversity of germplasm utilized in rootstock breeding, significantly increases the number of new hybrids evaluated concurrently, and greatly reduces the time from cross to potential cultivar release. We describe the key components and methodologies of this new strategy, termed “SuperSour”, along with reference to the historical favorite rootstock sour orange (C. aurantium), and previous methods employed in citrus rootstock breeding. Rootstock propagation by cuttings and tissue culture is one key to the new strategy, and by avoiding the need for nucellar seeds, eliminates the 6-15-year delay in testing while waiting for new hybrids to fruit. In addition, avoiding selection of parents and progeny based on nucellar polyembryony vastly expands the potential genepool for use in rootstock improvement. Fifteen new field trials with 350 new hybrid rootstocks have been established under the SuperSour strategy in the last eight years. Detailed multi-year performance data from the trials will be used to identify superior rootstocks for commercial release, and to map important traits and develop molecular markers for the next generation of rootstock development. Results from two of these multiyear replicated field trials with sweet orange scion are presented to illustrate performance of 97 new hybrid rootstocks relative to four commercial rootstocks. Through the first 7 years in the field with endemic HLB, many of the new SuperSour hybrid rootstocks exhibit superior fruit yield, yield efficiency, canopy health, and fruit quality, as compared with the standard rootstocks.